Effects of sodium bicarbonate intake on performance in middle distancerunning with additional weight - PELVAN, SERDAR ORKUN (My University, 2023)
In this study, the effects of external sodium bicarbonate (NaHCO3) intake on performance in middledistance running with additional weight were investigated. Male athletes (n=13) with an average age of 26.38 ± 2.81 (years) and 5.92 ± 1.84 (years) of sport experience, and with bodyweight of 77.83 ± 8.13 (kg) involved voluntarily. Performance measurements were made by Cooper run test, while the athletes carried a load with the additional weight of 20% of their body weight. One group of athletes were given 300 ml fruit juice mixed with 20 gr. starch and the other group was given sodium bicarbonate (NaHCO3) at a dosage of 0.3 g / kg mixed with 300 ml fruit juice given as single-blind. Anthropometric measurements, blood lactate, running distance and heart rate were measured on the test days. The analysis was examined by repetitive measures ANOVA at p<0.05 significance level via SPSS 14 program. The results revealed that running distances with the intake of sodium bicarbonate (NaHCO3) increased and there was a significant difference in blood lactate levels (p <0.05 ).In the Cooper test, it was observed that the performance of athletes who run with 20% of their body weight and use sodium bicarbonate (NaHCO3) increases.

Çalışmamızda ilave ağırlık ile yapılan orta mesafe koşularında dışarıdan sodyum bikarbonat (NaHCO3) alınmasının performansa etkileri araştırılmıştır. Çalışmaya ortalama yaşları 26,38 ± 2,81 (yıl), spor yaşları 5,92 ± 1,84 (yıl), vücut ağırlığı 77.83 ± 8.13 (kg) olan erkek sporcular (n=13) gönüllü olarak katılmıştır. Çalışmada sporcuların vücut ağırlığının yüzde yirmisine (%20) eşit olan ağırlık sırt çantasına içerisine konularak yapılan Cooper koşu testi ile performans ölçümleri yapılmıştır. Sporculara koşudan 90 dk önce plasebo grubuna 20 gr. nişasta karıştırılmış 300 ml meyve suyu ve diğer gruba ise 0,3 gr/kg dozajında sodyum bikarbonat (NaHCO3) 300 ml meyve suyuna karıştırılarak tek kör (single blind) yöntemi uygulanarak verilmiştir. Test günlerinde antropometrik ölçümler, kan laktatı, koşu mesafesi ve kalp atım hızları ölçülmüştür. Çalışmada elde edilen sonuçlar SPSS 14 programı kullanılarak Tekrarlayan Ölçümler ANOVA analizi ile 0,05 anlamlılık düzeyinde incelenmiştir. Ölçümler sonucunda dışarıdan sodyum bikarbonat (NaHCO3) alımında koşu mesafelerin arttığı ve kan laktat seviyelerinde anlamlı bir fark olduğu bulunmuştur (p<0,05). Sporcuların vücut ağırlığının yüzde yirmisi oranında ilave ağırlık kullanarak yaptığı Cooper koşu testinde sodyum bikarbonat (NaHCO3) kullanan sporcularda performans artışı meydana gelmiştir.
İlave ağırlık ile yapılan orta mesafe koşularda sodyum bikarbonat alımının performans üzerine etkisi
Keywords: Sodyum Bikarbonat; İlave Ağırlık; Cooper Testi; Performans; Taktik Atlet; Sodium Bicarbonate; Additional Weight; Cooper Test; Performance; Tactical Athlete